PEMODELAN SISTEM USAHATANI TERINTEGRASI UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - Budiasa, I Wayan (Bumi Lestari; Vol 13 No 1 (2013), 2013)
Abstract The objective of this study is to develop the optimal solution model for food production technology of integrated farming system (SIMANTRI) to support sustainable agriculture in Bali. Primary data under survey method towards 20 farmers of the SIMANTRI 068 in Buleleng Regency and secondary data from appropriate sources were used to specify parameters of the model. Linear programming approach was used to analyze constrained optimization problem of the model by using BLPX88 package program. A small farming system with farm scale of 0.58 hectare, which integrates food and horticulture crops and bali cattle, was optimally operated by farmer. It is indicated by optimal solution of the model which conforms to observed behavior. The maximum farming system’ income that was generated from the optimal model was Rp21,658,160 per annum. The integrated farming system (SIMANTRI 068) is potentially sustainable since it can fulfil sustainability criteria: economically viable, environmentally sound, socially acceptable, technically and culturally appropriate.
Keywords: Key words: farm modeling; linear programming; sustainable agriculture